O medo do desemprego e a(s) nova(s) organizações de trabalho The fear of the unemployment and the new corporation - Laura Marques Castelhano (Psicologia & Sociedade, 2005)
O objetivo deste artigo é discutir como o aumento do desemprego altera as relações entre o sujeito e a organização, intensificando o medo no ambiente de trabalho. Demonstra-se como o medo de perder o emprego, torna o trabalhador mais vulnerável e sujeito a formas de dominação e controle, e produz efeitos como o aumento do sofrimento, a neutralização da mobilização coletiva e o individualismo. The objective of this article is to discuss how the unemployment increase alters the relationship between the subject and the organization, intensifying the fear factor in the work environment. The study demonstrates how the fear of losing the job leads the worker to become more vulnerable and susceptible to forms of domination and control. This fear also produces effects such as the increase of suffering, the neutralization of the collective mobilization and the individualism.